Factors that Affects Tourist Intentions in the Conditions of the Covid-19 Pandemic - Strugar Jelača, Maja; Bjekić, Radmila; Marić, Slobodan (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2021)
The COVID-19 pandemic caused the crisis ?round the world. The biggest negative effects were felt by organizations operating in the field of tourism. New changes in tourist preferences affect the creation of completely new beliefs and patterns of tourist behavior around the world. The aim of this paper is to determine the changes in the pattern of behavior of residents in the territory of AP Vojvodina from the point of view of using tourist services. Within the work, 50 residents of AP Vojvodina were interviewed. The intention to use tourist services was analyzed, depending on the psychological impact, economic impact, recession, travel risk, tourist destination risk, caused by the appearance of the COVID-19 pandemic. A questionnaire by Pappas N., consisting of 37 statements, was used to conduct the mentioned analysis. By applying the correlation analysis, the connections between the mentioned impacts and risks were determined, on the one hand, and the intention of the residents to make a decision on a tourist trip during 2021, on the other hand. Due to the evident change in the intentions of residents from the point of view of using tourist services, there is more than ever a need to redefine the existing business strategy of the company within the tourism sector. There is a need to find new ways to organize a safe form of tourism. Virtual tourism as one of such ways has gained in importance especially under the influence of social distancing and is the only one who could allow the transfer of culture and habits of the population of tourist destinations in the safe way.